Alkali activated slag foams: The effect of the alkali reaction on foam characteristics. (20th March 2017) - Hajimohammadi, Ailar; Ngo, Tuan; Mendis, Priyan; Kashani, Alireza; van Deventer, Jannie S.J.
Abstract: The effect of the alkali activation reaction on the characteristics of slag-based foams made by the mechanical foaming technique is investigated. The mechanical foaming method is selected in order to control the density and quantity of the pre-made foam and minimise the impact of alkali reaction on the amount of initial foaming. Despite the similarity of the pre-made foams mixed with the altered binder formulae, a change in the alkali reaction is shown to affect the pore size distribution, pore homogeneity, density and properties of the inorganic foams. The water content of the binders is shown to be the key factor affecting the bubble breakage and foam sorting during the mechanical mixing stage. Later in the reaction, the reaction rate of the binders and the size of the gel particulates govern the pore size distribution and directional homogeneity of pore distribution within the matrix. Also, the reaction rate and the size of the gel particulates regulate the final density of the inorganic foams. The thermal conductivity is higher in the samples with higher density, but it is largely affected by the directional homogeneity of pore distribution. Apart from the strength of binding matrix and size distribution of pores, the directional homogeneity of porosity is shown to be the vital factor for high strength development. Graphical abstract: Same amount of premade foam with the same density is added to three different mix formulations of alkali activated slag binders, and the impact of alkali reaction on foam characteristics is investigated. It is shown that characteristics of the inorganic foams don't have to be controlled by the quality and quantity of pre-made foam blended with them. It is possible to control the density and properties of inorganic binders by manipulating their mix formulation. Highlights: Alkali reaction can be altered to control the characteristics of slag-based foams. The water content is the key factor in bubble arrangement during mixing stage. Thermal conductivity is largely affected by homogeneity of pore distribution. Homogeneity of porosity is the vital factor for high strength development.